Between limits and possibilities of school geography - Teixeira Viana, João Paulo (Revista Ensino de Geografia (Recife), 2020)
This study aims to build a comparative analysis of Brazilian education through data from decades, using as a basis the important postulate entitled "The Citizen of Paper" by the author Gilberto Dimenstein, a book that seeks to trace the reality ofBrazilian society through statistical data from the 1990s about the problems that plague the country. Thus, the work has in its development the updating and comparison between the data in Dimenstein's book and current statistics, however, directed to the aspect that is portrayed in the book, being education. The data were collected at the Brazilian Institute of Geography and Statistics (IBGE), in its SIDRA database, at the Ministry of Education (MEC), at the National Institute of Studies and Research Anísio Teixeira (INEP), and among others. Finally, with this data it was possible to build comparative maps of the Brazilian educational reality in themes such as: illiteracy, school dropout, number of basic education enrollments, among other themes, making it possible to understand Brazilian education between two distinct decades. As expected results, the data showed that education in Brazil presented great social advances, especially in those related to illiteracy, however, there is still a picture of challenges to be overcome, and as we will see it is through education that the development of a nation is possible.